Training on Nugget Making and Coaching for the Board Members of Gereja Kristen Muria Indonesia, Padang Cermin Region, Pesawaran Regency, Lampung - Sunarto, Sunarto; Purba, Dreitsohn Franklyn; Prianto, Robi; Tampubolon, Yohanes Hasiholan; Tiladuru, Vena Melinda (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower the members of GKMI Lembah Pujian in Padang Cermin, Pesawaran District, through a training program on nugget production. The majority of the church members work as farmers, and this skill is expected to enhance their income and improve their economic welfare. The nugget-making process involves utilizing locally available ingredients such as chicken, eggs, tapioca flour, and breadcrumbs, combined with seasonings to create a high-value product. This training not only provides practical skills in food processing but also opens opportunities for small-scale businesses that can be developed by the church members. The initiative is expected to help participants create sustainable income sources, improve their living standards, and support the church’s service activities. This program demonstrates the potential of food processing as an effective means of community empowerment and economic development.